2008
DOI: 10.1186/1477-7819-6-134
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical oncocytic carcinoma with recurrent metastases: a case report and review of the literature

Abstract: Background: Adrenal cortex oncocytic carcinoma (AOC) represents an exceptional pathological entity, since only 22 cases have been documented in the literature so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
(37 reference statements)
0
8
0
11
Order By: Relevance
“…According to the currently used classification, there are three histological categories: pure and benign oncocytoma, oncocytic neoplasm of uncertain malignant potential [36][37][38] and oncocytic carcinoma [39][40][41][42] .…”
Section: Histologymentioning
confidence: 99%
“…According to the currently used classification, there are three histological categories: pure and benign oncocytoma, oncocytic neoplasm of uncertain malignant potential [36][37][38] and oncocytic carcinoma [39][40][41][42] .…”
Section: Histologymentioning
confidence: 99%
“…In 21.9% of cases, diagnosis was performed by abdominal pain or palpable mass and in 21.9% of cases by excessive hormone secretion symptoms (36.8%). In 10 cases, there was evidence of metastasis , and in two cases, there was invasion into the inferior vena cava , while seven cases presented tumor recurrence after resection .…”
Section: Discussionmentioning
confidence: 99%
“…It can also be found in pituitary, eyelids, parathyroid, thymus, spinal cord, and other parts. [ 1 , 5 , 6 ] So, the adrenal cortical oncocytoma is a rare disease with an unknown incidence. No identified environmental or genetic risk factor was reported for the etiology of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Although 3 cases were diagnosed malignant potential in condition that they met the secondary criteria, we did not see any metastasis and recurrence during the follow-up. Argyriou et al [ 5 ] reported 1 case with a tumor relapse, and it was the only 1 case in the literature. However, the patient had a history of adrenocortical carcinoma, and the diagnosis criteria used by the author aroused a controversy.…”
Section: Discussionmentioning
confidence: 99%